Development and testing of a pyro-driven launcher for harpoon-based comet sample acquisition. (November 2018) - Völk, Stefan; Ulamec, Stephan; Biele, Jens; Hecht, Matthias; Lell, Peter; Fleischmann, Josef; Althapp, Sebastian; Grebenstein, Markus; Nuth, Joseph A.; Wegel, Donald C.; Smith, Walter F.; Purves, Lloyd R.; et al.
Abstract: The CORSAIR (COmet Rendezvous, Sample Acquisition, Investigation, and Return) mission was a proposal for the NASA New Frontiers program. It belongs to the Comet Surface Sample Return mission theme which focuses on acquiring and returning to Earth a macroscopic sample from the surface of a comet nucleus. CORSAIR uses a harpoon-based Sample Acquisition System (SAS) with the spacecraft hovering several meters above the comet surface. This stand-off strategy overcomes disadvantages of other systems such as drills. Since comets are low gravity objects, those techniques would require anchoring before sampling, which is not necessary here. Moreover, the harpoon-based system allows for acquiring several samples from different locations on the comet maximizing the scientific output of the mission. Each SAS assembly consists of a pyro-driven launcher, a Sample Acquisition and Retrieval Projectile (SARP) and a retraction system using a deployable composite boom structure. In order to collect enough cometary material, the launcher has to provide the required kinetic energy to the SARP. Due to high energy densities, pyrotechnically actuated devices ultimately reduce the overall system mass and dimensions. First, the scientific and technological background of the CORSAIR mission is explained. Then, an overview of the development, design and testing of the launcher is given. Finally, the launcher theory is introduced explaining the entire reaction chain: initiation → gas dynamics → SARP motion. Highlights: A harpoon-based comet surface sampling method is proposed. Sampling is safely conducted without landing using a stand-off strategy. A pyrotechnic launcher transfers the required momentum to the sampling device. The used high-low pressure system optimizes the motion profile and reduces mass.